Bacteriological control of meat. Proposals relative to the amendment of the existing legislation - ΣΚΟΥΝΤΖΟΣ Κ.; ΠΑΠΑΔΙΑ Α.; ΓΙΑΝΝΟΥΣΗΣ Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
The authors are reviewing the norms used in different countries for the hygiene and the technology of cow’s meat. They are also reffering to the media used for the bacteriological control of meat.